Celiac Crisis Presenting with Refractory Hypokalemia and Bleeding Diathesis - Mehta, S; Jain, J; Mulye, S (Kathmandu University Medical Journal, 2015)
Celiac disease is an immune mediated disorder elicited by the ingestion of gluten in genetically susceptible person and associated with some HLA subtypes. It is characterized by chronic inflammation of small intestine associated with villous atrophy. Symptoms usually appear when weaning from breast milk is done and gluten is introduced in diet. Failures to thrive, chronic diarrhea, vomiting abdominal distension are usual symptoms. Celiac crisis is rare but well known complication of celiac disease presenting with various systemic and metabolic manifestations like hypokalemia, hyponatremia, shock and bleeding diathesis. Celiac crisis usually has some underlying precipitating factor and is more common in patient with noncompliance with gluten free diet. We report a case of 14 year and three months old female child, a known case of celiac disease having the poor compliance with gluten free diet, presenting in celiac crisis with shock, refractory hypokalemia and bleeding diathesis. Kathmandu University Medical Journal Vol.12(4) 2014; 296-297